ANALISIS KEMAMPUAN LITERASI STATISTIS DALAM PEMBELAJARAN MATEMATIKA DI MASA PANDEMI - Fiqih Fadillah; Dadang Rahman Munandar (IKIP Siliwangi, 2021)
Statistical literacy skills are an important aspect that students need to have in building life skills during the pandemic. An alternative that can be done in building statistical literacy skills is through learning mathematics, especially in statistical material. This article aims to describe the statistical literacy skills of students during online learning during the pandemic, as well as to describe the difficulties experienced by students in solving problems related to statistical concepts. This research was conducted using a qualitative approach with a descriptive method. The subjects in this study were 25 students of class X at SMAN 1 Setu Bekasi. The data collection technique was carried out using a statistical literacy ability test instrument with the scope of the test material, namely Statistical material. This study resulted in the acquisition of the percentage of students' statistical literacy skills which were still low in each indicator. The ability of students to interpret the data indicators has the largest percentage, which is 68%. And on the indicator presenting the data, it gets the lowest percentage, which is 46%. Some students still cannot understand statistical concepts well so they are not able to present data and provide statistical conclusions correctly.